Solar Cell Outdoor Bench Design In Open Public Space For Gadged Charging Station - Hamid, Abdul; Yusuf, Muhammad; Setyarini, Rianti; Primayanda, Eritrian Bisma; Muna, Naila Sa'adatil (Politeknik Negeri Semarang, 2023)
Abstract””The increase in electrical energy is increasing along with the needs of rapidly developing technology. However electricity technology also produces negative impacts such as air and noise pollution caused by power plants. Electrical energy generation is still mostly generated from fossil fuels. A solution that can overcome this problem is to switch to more environmentally friendly electricity technology, such as solar panels. This solar powet plant can be used as an option as a charging energy source in a smart furniture. This research aims to make Solar Cell Powered Outdoor Charging Bench technology. This bench has several important components, namely: Solar Panel, Solar Charging Controller (SSC), inverter, and battery. This Outdoor Bench is placed in an open place such as a park, Public Open Space and so on which will be used as a charging place for cellphones or laptops. The way this bench works starts with the absorption of solar heat by solar panels on the roof of the bench which is converted into low-voltage electrical energy, then this energy is stored in a dry battery (battery) through SSC, low-voltage electricity is converted through an inverter, and this inverter channels electricity to the socket, so that the charging bench can be used properly.